Granica na Odrze i Nysie. Podstawy prawne oraz krytyczna analiza doktryn rewizjonistycznych: [Oder-Neisse line. Legal foundations and critical analysis of revanshist doctrines] (Studia Prawnicze / The Legal Studies, 1964)
The first chapter of this article is a brief summary of the legal foundations of the Oder-Neisse Line: Potsdam Agreement dated 2 August 1945, an agreement on the demarcation of the established and existing Polish-German state border concluded between Poland and the German Democratic Republic and signed in Zgorzelec on 6 July 1950, and an agreement on the demarcation implementation in the places of the Polish-German border signed on 27 January 1951 in Frankfurt (Oder).Contrary to the above agreements, the Federal Republic of Germany has not recognized the established and existing Polish-German border, but also constantly pursues a policy of territorial revanchism ignoring and considering null and void both the Potsdam decisions of the anti-Hitler coalition and bilateral border agreements between Poland and the GDR. According to West German, the Potsdam Agreement is not legally valid for Germany, or is misinterpreted on the issue concerning the provisions on the Oder-Neisse Line. At the same time, the FRG does not recognize the GDR existence and, therefore, according to West German politicians, Poland’s agreements with the GDR have no legal significance and are void.The second chapter sets out and analyses the revanchist views which dominate in the West German science of international law and develop the above-mentioned official theses of the Federal Republic of Germany. The first concept tries to prove that the Potsdam Agreement is not valid for Germany and contravenes the international law. The main argument was that, since Germany did not take part in signing the Potsdam Agreement, it was nothing more than res inter alios acta for them. The author proves that these provisions have no basis. The legal basis for the disposal of German territory by the Allies was act of the unconditional surrender. By signing the acts of unconditional surrender of all German armed forces, Germany expressed its consent to any decisions of the Allies announced in the blank article 4 of these acts and subsequently formulated in art. 16 of Declaration on the supreme power in which the Allies, in particular, specified that they would take all possible measures as they saw fit to secure future peace and safety; Germany should not and could not even be a party to the Potsdam Agreement, because there was no all-German government at the time of its signing. The author also resolutely rejects the theses about the existence of alleged contradictions between the Potsdam Agreement, on the one hand, and the Atlantic Charter and the Charter of the United Nations, on the other hand. From a formal point of view, the UN Charter clearly excludes the questions of eliminating the consequences of the Second World War from the UN sphere of competence.The second concept tries to prove that the Polish-German Agreements on the demarcation of the border line are invalid and not binding, since the German Democratic Republic is not a state and, therefore, does not have jus tractatum. In particular, these theories are based on the absurd assertion that there is only one German State (FRG) entitled to represent Germany. As evidence of the GDR “non-existence”, they also refer to the constitutive theory of recognition taking into account the fact that the Western states have not recognized the GDR. In contrast to the governments of the FRG and most of the capitalist countries, the socialist countries recognize the existence of two German states. The thesis about the existence of two German states is approved by the socialist science and partly by the science of Western countries, in particular, by French science.The third chapter describes how the issue of the Oder-Neisse Line was covered at the Allied conferences in Tehran (1943), Yalta (1945) and Potsdam (1945).The fourth chapter is devoted to the legal content of the Potsdam Agreement. The author states that the Potsdam Agreement is an international agreement for its counterparties, as a result of which it is subject to the normal methods of the international agreement interpretation. At the same time, in the light of the acts preceding the Potsdam Agreement, it is a solution that is binding on Germany. The Potsdam Agreement as an agreement between the Allied Powers expresses their common will, and all later speculations that the consent of the Western Powers has been based on the coercion or error are groundless. It is true that Poland did not sign the Potsdam Agreement but took part in its preparation and conclusion, gave its consent to the territorial regulations with all clarity and per fakta concludentia, as well as acquired certain rights under the agreement. Thus, Poland is a ”party de facto” of the Potsdam agreement. If a third state has taken up the rights stipulated in its favour in a clear and implied manner, they may not be changed by the signatories of the agreement without its consent. According to these principles of international law, Poland irrevocably acquired the rights granted by the Potsdam Agreement.The author proves in detail that the provisions of the Potsdam Agreement concerning the Oder-Neisse Line are unequivocal. This follows from the logical and systematic interpretation of the Potsdam Agreement and from the fact of the resettlement of Germans from the Reunited Western States, which has been provided for by the Potsdam Agreement and then carried out with the consent of all the Allied Powers. Any other interpretation would lead to the absurd conclusion that the resettlement of millions of people was temporary.The last fifth chapter is entitled: The Polish-German Border and the Peace Treaty with Germany. The author analyses Soviet proposals for a peace treaty with Germany and indicates that the conclusion of such a treaty would deal a heavy blow to the West German revanchism policy.